Gender, Class, Race, and Reform in the Progressive Era. - Frankel, Noralee, 1950-; Dye, Nancy Schrom, 1947-2015 (The University Press of Kentucky, 1991)
In this collection of informative essays, Noralee Frankel and Nancy S. Dye bring together work by such notable scholars as Ellen Carol DuBois, Alice Kessler-Harris, Barbara Sicherman, and Rosalyn Terborg-Penn to illuminate the lives and labor of American women from the late nineteenth century to the early 1920s. Revealing the intersections of gender, race, ethnicity, and social class, the authors explore women's accomplishments in changing welfare and labor legislation; early twentieth century feminism and women's suffrage; women in industry and the work force; the relationship between family.